The awareness and acceptance of anti-COVID 19 vaccination in adolescence - Vita Cupertino; Elena Bozzola; Giampaolo De Luca; Emanuela Del Giudice; Giuseppe De Martino; Piero Cannataro; Alberto Eugenio Tozzi; Giovanni Corsello (BMC, 2022)
Abstract Background COVID-19 had devastating effects on children's and adolescents' life, including neuropsychological impairment, discontinuation of social life and education. Since June 2021, antiCOVID19 vaccination has become available to adolescents in Italy up to 12 years and since December 2021 to children aged more than 5 years. The pediatric population represents a challenging target for vaccination. Aim of the study is to perform a survey among adolescents to explore factors associated with COVID 19 immunization and their perceptions about COVID-19 vaccines. Methods Italian students aged 10-17 years were invited to participate in an anonymous online survey regarding their immunization against COVID-19 and their opinion on the immunization practice through a web link to the questionnaire. The study period was March-June 2022. Statistical analysis was performed with SPSS v 21. Results In the study period, 895 students entered the survey. A total of 87.3% of respondents were immunized against SARS-CoV2. The most important predictors of being immunized against SARS-CoV2 were having both parents immunized (p < 0, 001) and being aged over 12 years. In the unvaccinated group, the decision was mostly influenced by the family (65.8%). Regardless the immunization status, respondents were willing to receive information about COVID 19 vaccination mostly by their family doctor (51.8%) and at school (28.9%). Conclusions Parents' decisions and attitudes strongly affected the immunization status of adolescents. Students' willing to receive COVID 19 vaccine information by family doctors and at school, underline the potential role of paediatricians and school educators in contributing to an increased vaccine coverage among the paediatric age.